2022
DOI: 10.3390/biom12020263
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking the Memory Component of Alzheimer’s Disease: Biological Processes and Pathways across Brain Regions

Abstract: Alzheimer’s Disease (AD) is a neurodegenerative disorder characterized by a progressive loss of memory and a general cognitive decline leading to dementia. AD is characterized by changes in the behavior of the genome and can be traced across multiple brain regions and cell types. It is mainly associated with β-amyloid deposits and tau protein misfolding, leading to neurofibrillary tangles. In recent years, however, research has shown that there is a high complexity of mechanisms involved in AD neurophysiology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 88 publications
0
1
0
Order By: Relevance
“…Another meta-analysis reported that variants of HPG axis-related genes, including those for corticotropin releasing hormone (CRH), CRH-binding protein, CRH-receptor, glucocorticoid and mineralocorticoid receptors, may differentially affect cognitive performance 33 . Global dysfunction of the HPG axis has often been described in the pathophysiology of Alzheimer’s disease 34 , 35 . Further, hypothalamic neuronal activities conduce to learning and memory independently of motivation, arousal, and anxiety 36 38 .…”
Section: Introductionmentioning
confidence: 99%
“…Another meta-analysis reported that variants of HPG axis-related genes, including those for corticotropin releasing hormone (CRH), CRH-binding protein, CRH-receptor, glucocorticoid and mineralocorticoid receptors, may differentially affect cognitive performance 33 . Global dysfunction of the HPG axis has often been described in the pathophysiology of Alzheimer’s disease 34 , 35 . Further, hypothalamic neuronal activities conduce to learning and memory independently of motivation, arousal, and anxiety 36 38 .…”
Section: Introductionmentioning
confidence: 99%